The use of geological 3D models to unravel Weichselian glacial history in Central Finnish Lapland and their application in groundwater flow modelling - Åberg, Annika (Helsingin yliopisto, 2021)
A proper risk assessment is part of mining projects from early stages to mine closure. Publicly companies present these assessments for example, in their Environmental Impact Assessment (EIA) reports. Potential risks related to water circulation can be investigated using groundwater flow modelling. In the present study, series of simple to more complex 3D geological models (GMs) were constructed from a Sakatti Ni-Cu-PGE deposit area in Sodankylä, northern Finnish Lapland to produce a numerical groundwater model. The 3D GMs were constructed utilizing data from outcrop investigations, various types of drillings and data obtained from non-destructive ground penetrating radar (GPR) soundings. In order to shed light on regional glacial history of central Finnish Lapland, outcrop studies, the existing till stratigraphy (GTK database) and LiDAR DEM imageries were used to investigate the sedimentary succession, interpret the depositional environments and reconstruct the Weichselian glacial flow patterns. The results of this study indicate that complex and detailed geological models are beneficial, especially in areas with a high hydraulic gradient, multiple units with differing hydraulic conductivity, and altered upper bedrock zone with variable degrees of weathering. Furthermore, it is essential to identify low conductive units, such as interbedded fine-grained till units, as well as high conductivity units such as fractures and faults, since they affect the location of recharge and discharge areas in hydrostratigraphic flow models. The 3D GMs constructed for the Sodankylä study area illustrate that altered bedrock, including fractured bedrock as well as grus- and clay-type weathered bedrock, is a prominent feature of the study area. The results of this study for example, indicate that fractured bedrock is more than 50 metres thick at the bend of the River Kitinen, while the grus-type weathered unit is on average 6 metres thick and the clay-type weathered unit 2.5 metres thick. Weak glacial erosion in the study area ...